2015
DOI: 10.1093/ndt/gfv425
|View full text |Cite
|
Sign up to set email alerts
|

Association between low birth weight and childhood-onset chronic kidney disease in Japan: a combined analysis of a nationwide survey for paediatric chronic kidney disease and the National Vital Statistics Report

Abstract: Both birth weight and gestational age were strongly associated with childhood-onset CKD in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 18 publications
0
26
0
7
Order By: Relevance
“…18,20,23 These associations are stronger in children and adolescents but continue up to an advanced age. 20,24,25 The link between developmental circumstances and risk of CKD appears, at least in part, to be mediated by altered renal development in utero or shortly after birth, which is associated with a reduced nephron number, subsequent hyperfiltration, and predisposition to hypertension. 26 Globally, approximately 10% of babies are born preterm, a proportion that is similar across income regions, 27 with the risk factors in developed countries including preeclampsia, prior preterm birth, advanced maternal age, chronic maternal illness, assisted reproduction, and multiple gestations.…”
Section: Primordial Prevention Of Ckdmentioning
confidence: 99%
“…18,20,23 These associations are stronger in children and adolescents but continue up to an advanced age. 20,24,25 The link between developmental circumstances and risk of CKD appears, at least in part, to be mediated by altered renal development in utero or shortly after birth, which is associated with a reduced nephron number, subsequent hyperfiltration, and predisposition to hypertension. 26 Globally, approximately 10% of babies are born preterm, a proportion that is similar across income regions, 27 with the risk factors in developed countries including preeclampsia, prior preterm birth, advanced maternal age, chronic maternal illness, assisted reproduction, and multiple gestations.…”
Section: Primordial Prevention Of Ckdmentioning
confidence: 99%
“…Maternal gestational diabetes and overweight or obesity were also significantly associated with childhood CKD (Hsu et al, 2014). In a Japanese study, 20% of childhood CKD was attributable to LBW or preterm birth (Hirano et al, 2016). Consistent with these observations, meta-analysis of 18 studies (including over 2 million individuals) reported a 70% increased risk of CKD (defined as albuminuria, reduced GFR or ESKD; OR 1.73, 95% CI 1.44-2.08) with LBW (White et al, 2009).…”
Section: Chronic Kidney Disease and End-stage Kidney Diseasementioning
confidence: 71%
“…Such individuals may have significant enough nephron deficits to initiate the cycle of progressive nephron loss. Among children attending pediatric renal clinics, strong associations between LBW and preterm birth and childhood CKD (including obstructive uropathy and aplasia/dysplasia) have been reported compared with the general pediatric population (Hsu et al, 2014;Hirano et al, 2016). Maternal gestational diabetes and overweight or obesity were also significantly associated with childhood CKD (Hsu et al, 2014).…”
Section: Chronic Kidney Disease and End-stage Kidney Diseasementioning
confidence: 99%
“…Hirano and colleagues demonstrated a strong association between birth weight and gestational age with childhood-onset CKD (36). In babies born at term, the majority of nephron formation occurs during the last trimester of gestation with nephrogenesis completed by week 36 of gestation (37).…”
Section: Epidemiological Studies Linking Birth Weight and Renal DImentioning
confidence: 99%